India agriculture and rural development, then and now - Quraishi, M. A. (Delhi, 1985)
The work is divided into three parts. Part I deals with 'waking up' of the sleeping giants of U. P., Part II 'Towards growth with Social Justice' compiles 21 papers including talks on the AIR and at Inter national Seminars given by the author as Additional Secretary, Government of India, Ministry of Agriculture.
Keywords: Uttar Pradesh agriculture economic aspects